Nontraditional Use of Biomass at Certified Forest Management Units: Forest Biomass for Energy Production and Carbon Emissions Reduction in Indonesia - Asep S. Suntana; Kristiina A. Vogt; Eric C. Turnblom; Daniel J. Vogt; Ravindra S. Upadhye (International Journal of Forestry Research)
Biomass conversion technologies that produce energy and reduce carbon emissions have become more feasible to develop. This paper analyzes the potential of converting biomass into biomethanol at forest management units experiencing three forest management practices (community-based forest management (CBFM), plantation forest (PF), and natural production forest (NPF)). Dry aboveground biomass collected varied considerably: 0.26–2.16 Mg/ha/year (CBFM), 8.08–8.35 Mg/ha/year (NPF), and 36.48–63.55 Mg/ha/year (PF). If 5% of the biomass was shifted to produce biomethanol for electricity production, the NPF and PF could provide continuous power to 138 and 2,762 households, respectively. Dedicating 5% of the biomass was not a viable option from one CBFM unit. However, if all biomasses were converted, the CBFM could provide electricity to 19–27 households. If 100% biomass from two selected PF was dedicated to biomethanol production: (1) 52,200–72,600 households could be provided electricity for one year; (2) 142–285% of the electricity demand in Jambi province could be satisfied; (3) all gasoline consumed in Jambi, in 2009, would be replaced. The net carbon emissions avoided could vary from 323 to 8,503 Mg when biomethanol was substituted for the natural gas methanol in fuel cells and from 294 to 7,730 Mg when it was used as a gasoline substitute.